Sustainability in action: policy, innovation, and Globalization’s influence on ecological footprint sub-components in G20 nation - Zhao, Xue; Wence, Yu; Haiyuan, Zhang (Frontiers in Environmental Science, 2025)
The rapid decline in environmental quality and the expanding ecological footprint (EFP) have become critical challenges, particularly for G20 nations that play a central role in global economic growth. This study investigates the determinants of the ecological footprint and its sub-components across 17 G20 countries over the period 1996 to 2021. Using advanced econometric methods such as cross-sectional dependence tests, slope homogeneity tests, unit root tests, cointegration tests, GMM, fixed effect models, and Granger causality analysis, this research provides a comprehensive analysis of key drivers. The findings highlight that technological advancements significantly reduce the ecological footprint, especially by enhancing environmental regulations and fostering sustainable practices. Human capital (HC) and institutional quality (IQ) emerge as critical contributors to sustainability, while globalization (GB) demonstrates mixed effects on ecological outcomes. Moreover, stringent environmental policies (EPS) exhibit robust bidirectional causal relationships with EFP, underscoring their vital role in mitigating environmental degradation. The study underscores the importance of targeted governmental interventions to promote technological innovation, strengthen institutional frameworks, and enforce rigorous environmental regulations. These insights provide actionable guidance for G20 nations to balance economic growth with environmental sustainability, aligning with global sustainability goals.